PERAN MEDIASI PERSEPSI KEADILAN GAJI DALAM PENGARUH PERSEPSI PERBEDAAN GAJI DAN PEMAHAMAN GAJI PADA KEPUASAN KERJA PEGAWAI NEGERI SIPIL - Ruhana Kurniawati; Mugi Harsono (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2016)
The aim of this study was to determine the employee’s pay perceptions and its relationships on job satisfaction as a form of local governments readiness in the implementation of the State Civil Apparatus (ASN) payroll system. The research design used in this research is descriptive and explanatory research. These respondent’s number are 150 employees with proportional random sampling technique. Data analysis technique used is Structural Equation Modeling (SEM).The results showed that the relationships of pay differences perception to pay fairness perception; pay fairness perception to job satisfaction; pay differences perception to job satisfaction; pay understanding perception to job satisfaction; and the mediating role of pay fairness perception on the relationship between pay differences perception to job satisfaction are proved to be significant, while the relationship of pay understanding perception to pay fairness perception and the mediating role of pay fairness perception on the relationship between pay understanding perception to job satisfaction are proved to be insignificant. More generally, the results of this study are expected to be in addition to the research literature as well as consideration for the organization, especially regarding pay perceptions and its relationships on job satisfaction.